Forensic Musicology and the Blurred Lines of Federal Copyright History - Leo, Katherine M. (Lexington Books, 2020)
Drawing on interdisciplinary research methods from musicological and legal scholarship, this book maps the historical terrain of forensic musicology. It examines the contributions of musical expert witnesses, their analytical techniques, and the issues they encounter assisting courts in clarifying the blurred lines of music copyright.